INSTITUTIONAL DYNAMICS OF AL-MUKMIN ISLAMIC BOARDING SCHOOL NGRUKI SURAKARTA (1972-2021) - Muhammad Luthfie Ramadhani; Hasan Asari; Khadijah Khadijah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
In the 1980s the Pesantren Al-Mukmin Ngruki began to get a negative image. The pesantren is considered a candidate for the Negara Islam Indonesia (NII), because there are two founding figures, namely Abdullah Sungkar and Abu Bakar Ba'asyir. They were plotted as individuals and extremists against the Kartosuwiryo movement. Various negative accusations made in various momentums and media as well as slanted views on the Pesantren Al-Mukmin Ngruki are still in the spotlight by various parties. In fact, until now various negative assumptions and accusations from both the eyes of the domestic and international public are still leveled at the Pesantren Al-Mukmin Ngruki, whereas this has never been proven at all. This study aims to find and analyze the historical institutional dynamics of the Pesantren Al-Mukmin Ngruki in 1972-2021. The research method used is qualitative with a historical approach using four steps, namely: heuristics, criticism, interpretation and historiography. The results of this study reveal that the historical institutional dynamics of the Pesantren Al-Mukmin Ngruki have a religious background. This means that the establishment of the Pesantren Al-Mukmin Ngruki was the result of the missionary journey of preachers in Surakarta, bearing in mind that during the transition period from the Old Order government to the New Order government, the area of Surakarta was a communist base and became the main target of Christianization which needed the attention of Muslims.